Impact of the Work Environment and Workload During the Covid-19 Pandemic on Teacher Performance (Case Study at SMA Negeri Kab. Tangerang) - Sunayah Sunayah; Armaini Akhirson (Dinasti Publisher, 2022)
This study examines how during the Covid-19 pandemic, changes in the work environment and workload have an impact on teacher performance. The scope of the research was conducted on teachers of physics, chemistry, and biology at SMA Negeri Kab. Tangerang, which was accredited A with a population of 123 and obtained 94 samples through the random sampling technique. The data used is primary data through the distribution of questionnaires to respondents after testing the quality of the instrument, namely the validity and reliability test. Test the quality of the data using the classical assumption test and hypothesis testing with multiple linear regression. The results showed that the work environment 39.7% had a significant impact, the workload 62.7% had a significant impact, as well as the work environment and workload simultaneously 80.9% had a significant impact.